Priming as a strategy to enhance stress tolerance in plants with focus on the role of Brassinosteroid related genes - Thoudal, Malin (SLU/Dept. of Plant Biology and Forest Genetics (until 131231), 2012)
It is of interest to gain knowledge of the mechanisms operating behind priming, an important possible strategy to help plants handle stress. The hypothesis is that priming of Arabidopsis thaliana, as a result of colonization of roots using the beneficial bacteria Bacillus amyloliquefaciens, stimulates Brassinosteroid (BR) synthesis in plants leading to plant growth promotion and improved defense responses. The beneficial bacterium B. amyloliquefaciens (strain UCMB5113) was used for priming of wild type Col-0 and different mutant lines of A. thaliana in order to study the gene expression of different BR-related genes using real-time PCR (qPCR). The BR-related genes DET2, BAK1, BRI1 and DWF1 were found to be involved in priming. Gene expression of BAK1, BRI1 and MPK4 was examined during Bacillus mediated priming and the result showed that Bacillus is likely to bind to BAK1 during priming. It was of interest to see whether a surface molecule on Bacillus could be responsible for priming. This was examined using heat killed Bacilli with focus on effects on BAK1 expression, compared with regular priming. The result showed that it is likely that a surface molecule on Bacillus is responsible for activation of BAK1 upon priming. Effects of herbivore and pathogen attack on A. thaliana during priming were also investigated using larvae of Spodoptera littoralis and Pseudomonas syringae pv. tomato strain DC3000, respectively. Both treatments indicated that the BR-related gene BAK1 is of great importance in defense responses to pathogen and herbivore attack. It was shown that primed plants were much more tolerant to different kinds of stress than control plants and could protect the plants to a certain degree from herbivory or disease.